Factors Affecting Student Interest Of Al-Quran Wonosobo Science University To Saving In A Syariah Bank - mahgalena mahgalena; Wahab Wahab; Choirul Huda (Universitas Islam Negeri (UIN) Walisongo Semarang, 2021)
Purpose - This study aims to examine the effect of knowledge, location and religiosity on the interest of students at the University of Sains Al-Quran Wonosobo to save in Islamic bank.Method - This research uses a type of field research with a quantitative approach. Sources of data in this study are primary data obtained from the results of a questionnaire by scoring using a likert scale. The population o this research is 100 students. In data analysis, the data analysis technique used is multiple linear regression analysis.Result - The result showed that knowledge had a significant effect on interest in saving in Islamic bank, while location and religiosity did not significantly influence the interest in saving at Islamic banks. Then knowledge, location and religiosity simultaneously affect the interest in saving at Islamic banks.Implication - This research can be used as input in getting customers with a high amount of savings in Islamic banks.Originality - This study looked at the factors that influence the interest of students at the University of Sains Al-Quran Wonosobo to save in Islamic banks This research can be used as input in getting customers with a high amount of savings in Islamic banks.. In this study focused on 3 variables, namely variables of knowledge, location and religiosity.